A Theoretical Study of SRPK Interaction with the Flexible Domains of Hepatitis B Capsids - Kim, Jehoon (The Biophysical Society, 2014)
Hepatitis B virus (HBV) controls genome encapsidation and reverse transcription from a single-stranded RNA to a double-stranded DNA through the flexible C-terminal domain (CTD) of the capsid proteins. Although the microscopic structure of the nucleocapsid plays a critical role in the life cycle of HBV, the location of CTD residues at different stages of viral replication remains poorly understood. In this work, we report the radial distributions of individual amino-acid residues of the CTD tails for both empty and RNA-containing HBV capsids by using a coarse-grained model for the key biological components and the classical density functional theory. The density functional theory calculations reveal substantial exposure of the CTD residues outside the capsid, in particular when it is devoid of any nucleic materials. The outermost layer of the capsid surface mainly consists of residues from (170)Ser-(175)Arg of the CTD tails, i.e., the serine-arginine protein kinase binding motif. The theoretical description corroborates recent in vitro studies that show a transient CTD distribution captured by serine-arginine protein kinase binding. We have also investigated the nucleocapsid structural changes due to phosphorylation of serine residues and shown a correlation between the CTD location and the internal distribution of RNA segments.